Effects of Housing Condition, Feeding Style and Age on Meat Colour, and Some Carcass Characteristics in Eastern Anatolian Red Bulls - Sadrettin Yüksel (Turkish Journal of Agriculture: Food Science and Technology, 2019)
This study was conducted to evaluate the muscles of the brisket region of the Eastern Anatolian Red (EAR) bulls in different ages subjected to different housing conditions and feeding style, and to determine the relationships among carcass traits, meat colour parameters and carcass measurements. Totally 25 bulls between 15 and 24 m of age were allocated to five groups (G1,G2,G3,G4,G5) according to feeding type, housing condition and age. The bulls were weighed fourteen days apart, feed consumption measurements were taken every morning, and slaughtered after 130 days of fattening. The differences were significant among G1-G3 for pelvic fat, total groups for conformation, among G1,G2-G3,G4,G5 for marbling, among G1,G2,G3-G4,G5 for LD area, among G1-G3,G5 for degree of fatten, among G1,G5-G2 for fat thickness over (LD) Longissimus Dorsi. The differences were significant in terms of meat colour parameters such as lightness (L*) in G1,G2,G3-G4,G5 and hue value (H*) in G1-G2,G3,G4,G5. Also, the differences among the groups are significant in terms of carcass length and width of the round. The correlation coefficients of carcass characteristic, colour score and conformation are negative with lightness (L*) and yellowness (b*). Degree fatten had a positive correlation with marbling score. Conformation were positively correlated with carcass length. Carcass ribeye area and L* showed a more desirable result in the G4 and G5 groups compared to other groups. Assessing the accumulated data of carcass traits with carcass components including carcass measurement during the slaughter or later phases of slaughter, it may be possible to use as a marker for the determining beef quality in EAR bulls.